Novel patient-specific 3D-virtual reality visualisation software (SpectoVR) for the planning of spine surgery: a case series of eight patients. Issue 4 (20th July 2020) - Croci, Davide Marco; Guzman, Raphael; Netzer, Cordula; Mariani, Luigi; Schaeren, Stefan; Cattin, Philippe C; Jost, Gregory F
Abstract : Background: Complex spine surgery requires a sound three-dimensional (3D) understanding of anatomy. Objective: Here, we report the preoperative use a of novel software (SpectoVR) that presents DICOM data as virtual 3D holograms. Methods: The software SpectoVR uses patient-specific DICOM data to render the anatomy as a hologram that is then viewed with a virtual reality (VR) headset. The surgeons used SpectoVR to prepare for complex surgeries. Results: Eight patients with the following diagnosis were presurgically studied with SpectoVR: (1) ankylosing spondylitis with fixed kyphotic cervical deformity treated with osteotomy reduction and cervicothoracic reconstruction; (2) persistent cervical foraminal stenosis after total disc replacement; (3) atlantoaxial osteoarthritis treated with C1–2 Magerl fixation; (4) adjacent segment degeneration with foraminal stenosis L5–S1; (5) C2–C4 chordoma; (6) spinal cord injury with rotational thoracolumbar fracture; (7) complex lumbopelvic deformity after prior hemipelvectomy for sarcoma and (8) atlantoaxial osteoarthritis and basilar impression in a patient with congenital craniosynostosis. Whereas VR did not omit the need for viewing the spine in the multiplane reconstruction mode, the authors feel that SpectoVR contributed to a better holistic understanding of the anatomy. Furthermore, positioning the spine like in the OR empowered the mental preparation for the surgery. Conclusion: Integrating SpectoVR in daily presurgical planning is feasible and appears to enhance the surgeon's awareness of the case.